Development of Teaching Material of Tissue Culture Media and Protoplast Culture Based on Scientific Literacy - Fauziyah Harahap; Candra Gunawan Sihombing (Undiksha, 2022)
This study aims to find out the feasibility of tissue culture books based on scientific literacy on the topic of tissue culture media and protoplast culture. The subjects in this study were lecturers of tissue culture courses and students majoring in Biology at Universitas Negeri Medan. This research is a study using the Dick and Carrey model which reaches the eighth step, namely formative evaluation where the process or program is considered complete. The results showed that (1) the assessment of material experts based on content, the suitability of the material with basic competencies and scientific literacy components obtained an average score 3,69 or 92,3% with very worthy criteria, (2) teachers of learning design experts based on material, systematic delivery of material, the efficiency of tissue culture and linguistic books obtained an average score 3,26 or 81,5% with worthy criteria, (3) an assessment by an expert lecturer on book layout design based on the cover design and book content design obtained an average score 3,77 or 94,2% with very worthy criteria, (4) the assessment by the lecturer in the tissue culture course obtained an average score 3,80 or 94,8% with very worthy criteria and (5) the assessment by students obtained an average score 3,52 or 90,6% included the very worthy criteria. So it can be said that the tissue culture textbook based on science literacy that has been developed is feasible according to material expert lecturers, learning designs, book layout designs, lecturers in tissue culture courses and students so that tissue culture books based on scientific literacy on the topic of tissue culture media and protoplast culture can used as a main/additional book for lecturers, students, readers in general and researchers who are interested in the field of tissue culture.